Open Source Website Literacy Learning Media to Improve Reading Literacy of Grade V Students - Wita, Wayan; Sanjaya, Dewa Bagus; Candiasa, I Made (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2025)
The results of the Computer Based National Assessment (ANBK) indicate that students continue to experience difficulties in reading literacy, underscoring the need for more interactive digital-based learning media innovations. This study aims to develop open-source website literacy to enhance students' reading literacy, focusing on criteria such as feasibility, practicality, and effectiveness. The research method uses the ADDIE development model. The subjects in this study were divided into 2 two groups in the feasibility test and the practicality test. Data were collected through various methods, including both non-test and test-based approaches, using questionnaires and multiple-choice questions. The feasibility test was conducted using the BSNP instrument, the practicality test was assessed with the User Experience Questionnaire (UEQ), and the effectiveness test was evaluated through a one-group pretest-posttest design. The results showed that open-source website literacy had a feasibility test with an average score of 3.82 (feasible category). The practicality test by teachers obtained a score of 2.46 (very practical), while students gave a score of 1.75 (practical). The effectiveness test, using the SPSS 26 t-test, yielded significant results. (2-tailed) = 0.000 < 0.05, indicating a statistically significant increase in students' reading literacy scores from pretest to posttest. The study's conclusion demonstrates that open-source website literacy is a feasible, practical, and effective approach to improving the reading literacy of fifth-grade elementary school students. The implications of this study confirm that integrating technology into literacy learning can increase student engagement and provide a more engaging learning experience.